ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD DI PT. RAVANA JAYA GRESIK - Latifah Nur Rohmah; Wasti Reviandani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research aimed to find out companies’ performance by using the balanced scorecard method for 3 years (2018-2021). The research was qualitative and the population was PT. Ravana Jaya, while the data sources are primary and secondary. The method of data collection was carried out using a questionnaire and interview. The data analysis technique uses balanced scorecard analysis with four perspectives, namely: financial perspective, customer perspective, internal business process perspective, and growth and learning. Based on the research result, for 3 years (2018-2020), it showed that: 1) financial perspective on ROA and ROE indicators is categorized as good while Sales Growth is categorized as poor due to some criteria which were given within the research. 2) Customer perspective shows that the indicators of the number of complaints, on time delivery and the level of customer satisfaction are categorized as good 3) Internal business process perspective shows that the company is able to overcome the number of customer complaints and the after-sales service indicators are categorized as good with the results of achieving service for customers. 4) Learning and growth perspectives on employee productivity as good and employee satisfaction are categorized while the employee retention rate is categorized as poor